Correlation Among Phenotypic Parameters Related to the Growth and Photosynthesis of Strawberry (Fragaria × ananassa Duch.) Grown Under Various Light Intensity Conditions - Choi, Hyo Gil (Frontiers in Plant Science, 2021)
The objective of this study was to investigate characteristics of phenotypic parameters such as physiology, yield, and fruit quality responses of strawberry (Fragaria × ananassa Duch) to various light intensity conditions, and to determine the correlations among these phenotypic parameters. Strawberry plants were cultivated in a smart greenhouse separated into four areas, three of which were completely shaded by curtains from 20:00 until 10:00 (SU10), 12:00 (SU12), and 14:00 (SU14), respectively. The fourth area was a non-shaded control treatment. The ambient light intensities during the experimental period for the control and SU10, SU12, and SU14 treatments were 1,285, 1,139, 770, and 364 mol·m−2·d−1, respectively. Strawberry plants grown under low light intensity conditions experienced decreases in photosynthetic rate, stomatal conductance, and sugar accumulation compared to the control. Petiole generation and fruit yield were also sharply decreased in proportion to the degree of decrease in light intensity. In contrast, photosynthetic pigment content was shown to increase under low light conditions. Organic acid contents (excluding acetic acid) and leaflet size did not change significantly under low light conditions compared to the control. Changes to light intensity are considered to induce changes to the phenotypic characteristics of strawberry plants to favor growth using the energy and carbon skeletons obtained through respiration and photosynthesis. In the SU14 treatment, where light intensity was drastically reduced, NPQ, qP, and RFd values as chlorophyll a fluorescence parameters were significantly lowered, which could indicate their measurement as an important technique to check the stress response of plants grown in low light conditions.